2003
DOI: 10.1590/s0021-75572003000400017
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de corpo estranho da via aérea de criança por broncoscopia através de traqueotomia ou traqueostomia

Abstract: Trabalho apresentado no XXIII Congresso Brasileiro de Cirurgia Pediátrica, realizado em Goiás, de 3 a 7 de novembro de 2002.Artigo submetido em 12.12.02, aceito em 26.03.03. ResumoObjetivo: a maioria dos corpos estranhos aspirados para a via aérea é removida através de endoscopia respiratória. Em situações raras, a retirada deste material tem que ser realizada sob controle endoscópico, através de traqueotomia ou traqueostomia. A seguir, relatamos casos de crianças cuja remoção de corpos estranhos aspirados par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
1
8
0
4
Order By: Relevance
“…(18) However, in the south of Brazil, diagnosis within the first 24 h has been described in most cases. (7,14) The accuracy of the initial diagnosis in the referral hospital studied here was, partially due to its being a specialized hospital, superior to that typically observed. (7,19) However, the exclusion of cases presenting negative endoscopic results contributed to such accuracy.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…(18) However, in the south of Brazil, diagnosis within the first 24 h has been described in most cases. (7,14) The accuracy of the initial diagnosis in the referral hospital studied here was, partially due to its being a specialized hospital, superior to that typically observed. (7,19) However, the exclusion of cases presenting negative endoscopic results contributed to such accuracy.…”
Section: Discussionmentioning
confidence: 69%
“…(1,7,11) However, we observed that the percentage of foreign bodies located in the larynx was high when compared with other locations, (1,7,14,26) a difference that has rarely been reported. (17,22) This finding might be specifically related to the aspiration of fish bones, which, due to their perforating characteristic, are frequently lodged in the larynx.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Entre os acidentes infantis mais freqüentes, a penetração de corpo estranho em orifício natural e sua ingestão ou inalação tem sido apontada por vários autores como sendo os cinco principais acidentes que ocorrem na população infantil 3,5,15 , atingindo principalmente os lactentes e menores de um ano, além de se constituir um acidente potencialmente fatal por causar, muitas vezes, obstrução das vias respiratórias 16,17 .…”
Section: Introductionunclassified
“…Vários trabalhos nacionais 17,18,19,20 e internacionais 21,22,23 apontam a presença de corpo estranho como importante causa de morbidade e mortalidade entre as crianças.…”
Section: Introductionunclassified